GE_GERICHTE P/17301/2022 vom 6. März 2025 - GE Cour de justice (2025)
CLASSEMENT DE LA PROCÉDURE;LÉSION CORPORELLE SIMPLE;VOIES DE FAIT;INJURE;MENACES ALARMANT LA POPULATION;CONTRAINTE(DROIT PÉNAL);PRESCRIPTION | CPP.319.al1.leta; CP.123.ch1; CP.126.ch1; CP.177.al1; CP.180.al1; CP.181; CP.109; CPP.319.al1.letd